W. B. Yeats e la cultura italiana - Fiorenzo, Fantaccini (Biblioteca di Studi di Filologia Moderna, 2009)
W. B. Yeats e la cultura italiana examines the "Italianism" of William Butler Yeats and the popularity of the Irish poet in Italian poetry and criticism. Appraising the presence and evocative influence of "learned Italian things" on the work of the Irish poet, through the study of his letters and as illustrated by the library conserved by his daughter Anne, and with constant references to the texts themselves, the Italian influences most evidently present in the work of the Irish Nobel winner are analysed and discussed. This first section of the book presents in its entirety the largely unpublished correspondence between Years and the philosopher Mario Manlio Rossi. Subsequently, observing the influence and the fascination exerted by the work of Yeats on Italian poets such as Montale, Solmi and Giudici, who even translated some of Yeats' poems, and Lucio Piccolo, who also had a brief epistolary exchange with the Irish poet, this too still partially unpublished, we arrive at a critical examination of the Italian reception of Yeats' works. W. B. Yeats e la cultura italiana is rounded off by an annotated bibliography of the translations and works of criticism which represents an important overview of the penetration of Yeats' work in Italy (1905-2005).